Who's bashing whom ? : trade conflicts in high-technology industries - Tyson, Laura D'Andrea (Institute for International Economics, 1993)
This study seeks to resolve the "free trade vs. managed trade" debate. It provides innovative recommendations for US policy based on detailed and rigorous case studies of high-technology trade conflicts between the United States, Japan and Europe in aircraft, telecommunications, electronics and supercomputers.The study addresses three key issues: What trade policy should the United States adopt to support its high-technology industries? What domestic policy initiatives are necessary to realize this goal? Are new international rules needed to reduce trade conflicts over high-technology industries? Tyson, formerly Chair of the President's Council of Economic Advisers, develops a "cautious activist" policy agenda to promote US competitiveness in high-technology sectors and to strengthen international rules to encourage trade and reduce conflicts among nations.